Protecting Buddhist Women from Muslim Men: "Love Jihad" and the Rise of Islamophobia in Myanmar - Frydenlund, Iselin (Religions, 2021)
Buddhist protectionism in contemporary Myanmar revolves around fears of the decline of Buddhism and deracination of the amyo (group/"race"). Buddhist protectionists and Burmese nationalists have declared Islam and Muslims the greatest threat to race and religion, and Myanmar has witnessed widespread distribution of anti-Islamic and anti-Muslim content, as well as massive violence against Muslim minority communities, the Rohingya in particular. The Indian neologism "Love Jihad" has scarce reference in contemporary Burmese Buddhist discourses, but, importantly, the tropes of aggressive male Muslim sexuality and (forced) conversion through marriage ("love jihad") have been one of the core issues in Buddhist protectionism in Myanmar. The article shows that such tropes of the threatening foreign male have strong historical legacies in Myanmar, going back to colonial Burma when Burmese concerns over Indian male immigrant workers resulted in both anti-Indian violence and anti-miscegenation laws. Importantly, however, compared to colonial Indophobia and military era xenophobic nationalism, contemporary constructions are informed by new political realities and global forces, which have changed Buddhist protectionist imaginaries of gender and sexuality in important ways. Building on Sara R. Farris’ concept of "femonationalism", and Rogers Brubaker’s concept of civilizationism, the article shows how Global Islamophobia, as well as global discourses on women’s rights and religious freedom, have informed Buddhist protectionism beyond ethnonationalism in the traditional sense.